Power Oscillation Analysis of PMSG Wind Power Generation System Considering Power Control Nonlinearity - Liu, Jianing; Yu, Miao; Zhao, Jinghan; Xia, Yanghong; Wei, Wei (Frontiers in Energy Research, 2022)
High proportion of renewable energy generation, especially wind power generation, has changed the dynamic behavior of power systems and leads to emerging stability issues such as oscillation accidents. The commonly used stability analysis methods based on linear system theory cannot tackle the influence of nonlinear elements in the control loop. To fill this gap, the describing function method is used to analyze the stability and power oscillations of a grid-connected permanent magnet synchronous generator (PMSG) wind power generation system in this paper. A complete PMSG system model is taken into consideration, including a wind turbine, a generator, a machine-side converter, a grid-side converter, and a weak grid. Particularly, the nonlinear element introduced by maximum power point tracking control in the power control loop is modeled and analyzed, and the influences of critical system parameters are studied. With the high accuracy of the describing function method, it is revealed that the machine-side converter mainly influences the oscillation amplitude, while the grid-side converter mainly influences the oscillation frequency. Furthermore, the following results can be obtained: 1) High bandwidth of maximum power point tracking control and rotation speed control may enlarge the oscillation amplitude, while a fast current loop of the machine-side converter is beneficial to the stability; 2) Grid-side voltage loop can significantly affect the frequency of the oscillation, and improper high bandwidth of a phase-locked loop (PLL) is harmful to system stability; 3) A stronger grid is not always beneficial to the system stability, and the influence of grid strength should be carefully analyzed and examined when nonlinear elements are considered. All analyses are verified by simulations based on MATLAB/Simulink.